2013
DOI: 10.1155/2013/628907
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Acupuncture Devices: Considerations for Acupuncture Research

Abstract: Determining an appropriate control for use in acupuncture research remains one of the largest methodological challenges acupuncture researchers face. In general, acupuncture controls fall under one of two categories: (1) sham acupuncture, in which the skin is punctured with real acupuncture needles either fully at nonacupoint locations or shallowly at acupoint locations or both and (2) placebo acupuncture, which utilizes nonpenetrating acupuncture devices. In this study, we will focus on non-penetrating placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 62 publications
3
67
0
1
Order By: Relevance
“…In this study, we found that combining acupuncture with fluoxetine can produce greater improvement in MDD patients, which is consistent with findings from previous studies investigating the combinative effects of acupuncture and other treatments (Duan et al, 2008; Y. Liu et al, 2008, Roschke et al, 2000, Zhang et al, 2009, Zhu et al, 2013). …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we found that combining acupuncture with fluoxetine can produce greater improvement in MDD patients, which is consistent with findings from previous studies investigating the combinative effects of acupuncture and other treatments (Duan et al, 2008; Y. Liu et al, 2008, Roschke et al, 2000, Zhang et al, 2009, Zhu et al, 2013). …”
Section: Discussionsupporting
confidence: 92%
“…However, antidepressant treatments may produce undesirable side effects and a delay in the onset of therapeutic action (Arroll et al, 2005, Zhu et al, 2013). In this study, we found that combining acupuncture with fluoxetine can produce greater improvement in MDD patients, which is consistent with findings from previous studies investigating the combinative effects of acupuncture and other treatments (Duan et al, 2008; Y.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have reported conflicting results when using a control group in research to test the true effectiveness of real acupuncture [1]. Some studies have consistently shown that both real and placebo acupuncture had advantages over untreated control groups [2, 3], while some studies have suggested that real acupuncture is more effective than placebo [4–6]; others have failed to show benefits of real acupuncture over placebo one [7–10].…”
Section: Introductionmentioning
confidence: 99%